Alkyl Substituted Anilines as Corrosion Inhibitor for N80 Steel in Hydrochloric Acid Medium - Haldar, N.; Shukla, H.S.; Udaybhanu, G. (Asian Journal of Chemistry, 2011)
The effect of 2-ethyl aniline and 2,4-dimethyl aniline as corrosion inhibitor for N80 steel in 15 % hydrochloric acid has been investigated by means of weight loss measurements and potentiodynamic polarization measurements. Corrosion inhibition ability of the compounds has been tested at different exposure periods (6 to 24 h) and at different temperatures (303 to 333 K and at 383 K). 2-Ethyl aniline has afforded maximum inhibition (88.3 %) at 6 h exposure period at room temperature. The adsorption of both the inhibitors is found to accord with Temkin adsorption isotherm. Potentiodynamic polarization study reveals that the tested inhibitors are mixed type inhibitor and preferentially act on cathodic areas. The characteristic shift of N-H and C-O bond frequencies towards lower side compared to that of the respective pure samples has been observed from FTIR studies which indicated the donation of electron pair through N atom and involvement of phenyl ring of the inhibitor molecule in the surface adsorption phenomena. SEM study has revealed formation of semi-globular inhibitor products on the metal surface. The comparisons of the protection efficiencies of these compounds according to their relative electron density on the adsorption centre and projected molecular area of the inhibitor molecules have been made.